The look of agricultural landscapes – How do non-crop landscape elements contribute to visual preferences in a large-scale agricultural landscape?. Issue 2 (14th March 2020) - Stokstad, Grete; Krøgli, Svein Olav; Dramstad, Wenche E.
ABSTRACT: Efficiency in agricultural food production has long been in focus and this has affected the spatial structure of agricultural land use. One outcome has been extensive criticism based on a wide range of negative consequences, such as for biodiversity, accessibility, cultural heritage, and aesthetics. In line with the European Landscape Convention (ELC), management of people's everyday landscapes is important. In Norway, agricultural landscapes are the 'everyday landscape' for a large proportion of the population. The aim of the article is to contribute to the understanding of landscape changes perceived as positive or negative by the inhabitants. The authors focused on grain-crop dominated landscapes and the impact of smaller non-crop elements on people's landscape preferences. They administered a photo-based questionnaire using manipulated photos to assess preferences for different agricultural landscapes. Additionally, people's perceived objectives for the agricultural sector and agriculture's primary functions were assessed. The results documented positive perceptions of added landscape elements and that people were both aware of and agreed on the multifunctional role of agriculture. The authors conclude that if the public's preferences are to be taken into consideration, such as during policymaking, it is important to maintain various landscape elements in the large-scale grain field landscapes of Norway.